Legionella on board trains: effectiveness of environmental surveillance and decontamination - Quaranta Gianluigi; Vincenti Sara; Ferriero Anna; Boninti Federica; Sezzatini Romina; Turnaturi Cinzia; Gliubizzi Maria; Munafò Elio; Ceccarelli Gianluca; Causarano Carmelo; Accorsi Massimo; Del Nord Pasquale; et al. (BMC, 2012)
Abstract Background Legionella pneumophila is increasingly recognised as a significant cause of sporadic and epidemic community-acquired and nosocomial pneumonia. Many studies describe the frequency and severity of Legionella spp. contamination in spa pools, natural pools, hotels and ships, but there is no study analysing the environmental monitoring of Legionella on board trains. The aims of the present study were to conduct periodic and precise environmental surveillance of Legionella spp. in water systems and water tanks that supply the toilet systems on trains, to assess the degree of contamination of such structures and to determine the effectiveness of decontamination. Methods A comparative pre-post ecological study was conducted from September 2006 to January 2011. A total of 1,245 water samples were collected from plumbing and toilet water tanks on passenger trains. The prevalence proportion of all positive samples was calculated. The unpaired t-test was performed to evaluate statistically significant differences between the mean load values before and after the decontamination procedures; statistical significance was set at p ≤ 0.05. Results In the pre-decontamination period, 58% of the water samples were positive for Legionella. Only Legionella pneumophila was identified: 55.84% were serogroup 1, 19.03% were serogroups 2-14 and 25.13% contained both serogroups. The mean bacterial load value was 2.14 × 103 CFU/L. During the post-decontamination period, 42.75% of water samples were positive for Legionella spp.; 98.76% were positive for Legionella pneumophila: 74.06% contained serogroup 1, 16.32% contained serogroups 2-14 and 9.62% contained both. The mean bacterial load in the post-decontamination period was 1.72 × 103 CFU/L. According to the t-test, there was a statistically significant decrease in total bacterial load until approximately one and a half year after beginning the decontamination programme (p = 0.0097). Conclusions This study indicates that systematic environmental surveillance could be a useful approach for assessing the risk of exposure to Legionella bacteria, which still represents a public health threat. According to the study results, an environmental surveillance programme, followed by decontamination procedures where necessary, would decrease the total bacterial count, protecting the health of travellers and workers.